Transfer Fee Regulations in European Football - Eberhard Feess; Gerd Muehlheusser (Institute for the Study of Labor (IZA), 2002)
We analyze the impact of three different transfer fee systems on payoffs, contract lengths, training and effort incentives in European football. The different regimes, being used until 1995 (?Pre-Bosman? or P), currently in use (?Bosman? or B), and recently approved (?Monti? or M) differ with respect to the transfer fee an initial club must accept in case of a transfer depending on whether a player has a valid contract or not. We show that the different systems differ only with respect to the contract length if the contract which maximizes the expected joint surplus of the initial club and the player is feasible under each system. Otherwise, regime P is strictly dominated by regime B in terms of expected social welfare. Regime M leads to higher effort but lower incentives to invest in training compared to system B.
Keywords: L83; K12; J41; 330; Labor contracts; Bosman judgement; transfer fees; breach of contract; investment incentives; general skills; externalities; Fußballsport; Arbeitsvertrag; Professioneller Sport; Vertragstheorie; Verhandlungstheorie; Abfindung; Sportler; Leistungsmotivation; Theorie; EU-Staaten; Ablösesumme